Complications of veno-arterial extracorporeal membrane oxygenation for refractory cardiogenic shock or cardiac arrest. Issue 1 (January 2020) - Lee, Soo Youn; Jeon, Ki-Hyun; Lee, Hyun Jong; Kim, Ji-Bak; Jang, Ho-Jun; Kim, Je Sang; Kim, Tae Hoon; Park, Jin-Sik; Choi, Rak Kyeong; Choi, Young Jin
Background: The frequency of using veno-arterial extracorporeal membrane oxygenation increased, especially in patients with refractory cardiogenic shock or cardiac arrest. However, data of complications of veno-arterial extracorporeal membrane oxygenation are lacking. This study sought to investigate the incidence of veno-arterial extracorporeal membrane oxygenation complications for acute myocardial infarction patients with refractory cardiogenic shock or cardiac arrest and its relationship with patient survival. Methods: This study included 151 consecutive patients who underwent veno-arterial extracorporeal membrane oxygenation between 2006 and 2018 at a single referral center. We divided the patients into those who survived for 30 days after veno-arterial extracorporeal membrane oxygenation ( n  = 57, 38%; group 1) and those who died within 30 days after veno-arterial extracorporeal membrane oxygenation support ( n  = 94, 62%; group 2). The major adverse clinical events associated with veno-arterial extracorporeal membrane oxygenation were defined as first occurrence of infection, major bleeding, and stroke. Results: Adverse clinical events associated with veno-arterial extracorporeal membrane oxygenation occurred in 34 (59.6%) and 56 (59.6%) patients in groups 1 and 2, respectively. Group 2 had more patients who underwent new renal replacement therapy (21.1% vs 37.2%, p  = 0.037). After multivariable analysis, cardiac arrest was independently associated with 30-day mortality (odds ratio = 3.6; 95% confidence interval = 1.7–7.63; p  = 0.001). After excluding patients who died within 48 h after undergoing veno-arterial extracorporeal membrane oxygenation, new renal replacement therapy (odds ratio = 4.47; 95% confidence interval = 1.58–12.61; p  = 0.005) and major adverse clinical events (odds ratio = 2.66; 95% confidence interval = 1.01–7.03; p  = 0.049) were independently associated with 30-day mortality. Conclusion: Although veno-arterial extracorporeal membrane oxygenation can improve the survival, it is associated with morbidity. Therefore, risk–benefit analysis for veno-arterial extracorporeal membrane oxygenation and prevention of complications are important to improve prognosis.